Os recursos didáticos no processo de alfabetização e letramento das crianças com Síndrome de Down - Peixoto, Ana Eline Ribeiro (Brasil, 2022)
Literacy and literacy are social roles for children that are essential for effective learning, as it is in the former that children expand their interaction with multiple languages and develop skills in reading, writing, textual interpretation and other languages. Thus, the school has the challenge of making all children literate, including children with disabilities. This qualitative approach research aimed to investigate how teaching resources can contribute to the literacy and literacy process of children with Down syndrome in the first year of elementary school. The research is based on studies by Freire (1984), Ludke and André (1986), Ferreiro and Teberoski (1991), Cruz (1997), Troncoso (1998), Schwartzman (1999), Moreira (2002), Mantoan (2003), Mills (2003), Kleiman (2005), Soares (2005, 2017), Haydt (2006), Freitas (2007), Gil (2008), Prodanov (2013), Lakatos and Marconi (2003), Lima (2016), Almeida (2017), Carvalho, MD, et al. (2017). The field research was carried out in a class of the first year of Elementary School of a Special Education School, which seeks to assist children, young people and adults with the most diverse disabilities located in the city of Parintins-AM from February 2nd to 13th, 2020. Participant observation of literacy practices of 8 (eight) children with Down's Syndrome and application of a questionnaire to 3(three) literacy teachers were used for data construction. The research results show that didactic resources are essential tools in the process of literacy and literacy for children with Down Syndrome, as they facilitate and enrich literacy practices, from the most tangible resources such as a sensory box or a stick handle, to technological resources such as educational games, because they contribute both to the acquisition of reading and writing skills and to the reading of the world of literacy students. Therefore, it is essential in literacy practices to use different teaching resources, considering the specificities and needs of children with Down Syndrome.